2021
DOI: 10.1002/adsc.202100644
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Fused Dihydroazepine Derivatives of Fullerenes by a Rh‐Catalyzed Cascade Process

Abstract: A synthetic methodology is reported that functionalizes C60 and C70 fullerenes with dihydroazepine rings by a cascade reaction encompassing a rhodium‐catalyzed cycloisomerization of 1,5‐bisallenes and a [4+2] cycloaddition. This transition metal‐catalyzed cascade reaction provides a versatile and step‐economical approach to the synthesis of 6,7‐membered polyheterocyclic fullerene adducts. Electrochemical characterization of the products obtained ventures their application in organic and perovskite photovoltaic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 76 publications
1
14
0
Order By: Relevance
“…In this study, the oxidative coupling between the allene moiety and the alkyne is preferred over the alkyne-alkyne coupling (TS(A2 A3), ΔG � = 19.0 kcal • mol À 1 ). [35][36][37][38] The coordination of DMAD to A3 gives A4, a 16electron square-pyramidal complex. The subsequent C�C insertion (Schore mechanism [48] ) is preferred to occur in the equatorial RhÀ C bond (TS 1 (A4 A5)) to produce the conjugated rhodacycloheptadiene A5.…”
Section: Updatesmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, the oxidative coupling between the allene moiety and the alkyne is preferred over the alkyne-alkyne coupling (TS(A2 A3), ΔG � = 19.0 kcal • mol À 1 ). [35][36][37][38] The coordination of DMAD to A3 gives A4, a 16electron square-pyramidal complex. The subsequent C�C insertion (Schore mechanism [48] ) is preferred to occur in the equatorial RhÀ C bond (TS 1 (A4 A5)) to produce the conjugated rhodacycloheptadiene A5.…”
Section: Updatesmentioning
confidence: 99%
“…Our group recently developed a cascade reaction involving 1,5-bisallenes and alkenes, [35] including C 60 , [36] to obtain fused 6,7-membered rings (Scheme 1d). The mechanism is postulated to proceed via an initial rhodium-catalysed cycloisomerization of the bisallene leading to a non-isolable 1,2-dimethylenecycloheptene scaffold, followed by a regioselective Diels-Alder reaction with alkenes in which the rhodium does not participate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, very interesting reactivities were observed (Scheme ). In the reaction of 1,5-bisallenes with alkenes, dihydroazepine- and dihydrooxepine-fused ring systems were obtained in good yields . Further mechanistic study by DFT calculations showed that the reaction took place through a rhodium-catalyzed cycloisomerization/Diels–Alder cascade encompassing oxidative coupling of the rhodium to the central carbon atoms of both allenes (intermediate I ) followed by a β-hydride elimination (intermediate II ) and reductive elimination of the rhodium to afford a non-isolable cycloheptatriene derivative III , which gave a further Diels–Alder reaction with the alkene (Scheme a).…”
Section: Introductionmentioning
confidence: 99%
“…Fullerenes are promising building blocks in biomedicine, organic and perovskite solar cells, (photo)­electrocatalytic systems, and simple structural scaffolds for functional materials due to their physicochemical, electrochemical, and photophysical properties and structural characteristics. Regioselective functionalization reactions of fullerenes have been actively sought after to improve the synthetic yield and the structural diversity of fullerene derivatives to realize their potential …”
mentioning
confidence: 99%